Peningkatan Keakurasian Produk Cetak 3D Printing Menggunakan Filamen PLA+ - Andimeri Andimeri; Muhammad Yunus; Pristiansyah Pristiansyah (Jurnal Inovasi Teknologi Terapan, 2026)
This study aims to improve the dimensional accuracy of printed products in the 3D Printing process using the Fused Deposition Modeling (FDM) method with PLA+ filament material. The research employed the Taguchi L9 (3²) experimental design to evaluate the influence of printing speed and layer height on the dimensional precision of the printed objects. Cube-shaped specimens measuring 20×20 mm were fabricated using an Ender 3 Pro printer and measured with a digital caliper of 0.02 mm accuracy. The results showed that the combination of a 0.10 mm layer height and 85 mm/s print speed produced the highest accuracy, with a minimal dimensional deviation of approximately ±0.05 mm from the nominal size. The Signal-to-Noise (S/N) Ratio analysis indicated that both parameters contributed equally to print quality. Therefore, optimizing printing parameters and utilizing PLA+ material effectively enhances dimensional precision, process stability, and geometric quality of 3D printed products. These findings can serve as a practical guideline for optimizing additive manufacturing processes based on the FDM technique.